Inaugurating a novel adjuvant therapy in urological cancers: Ferroptosis - Xie, Zhaoxiang; Zhou, Qianghua; Qiu, Cheng; Zhu, Dingjun; Li, Kaiwen; Huang, Hai (Cancer pathogenesis and therapy, 2023)
Ferroptosis, a distinctive form of programmed cell death, is involved in numerous diseases with specific characteristics, including certain cell morphology, functions, biochemistry, and genetics, that differ from other forms of programmed cell death, such as apoptosis. Many studies have explored ferroptosis and its associated mechanisms, drugs, and clinical applications in diseases such as kidney injury, stroke, ischemia-reperfusion injury, and prostate cancer. In this review, we summarize the regulatory mechanisms of some ferroptosis inducers, such as enzalutamide and erastin. These are current research focuses and have already been studied extensively. In summary, this review focuses on the use of ferroptosis induction as a therapeutic strategy for treating tumors of the urinary system. [Display omitted] •It is a detailed timeline that discovery and development of the main mechanism and participators on ferroptosis.•The summary, nanoparticles in ferroptosis applications, was a highlight in the review. It is a significant assist to create various nanoparticles that could induce ferroptosis.•There are plenty of logical graphics to summarize the current drugs and small-molecule inhibitors which could induce ferroptosis.